2012
DOI: 10.1080/10803548.2012.11076918
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Coupling Forces Woodcutters Exert on Saws in Real Working Conditions

Abstract: Prolonged exposure to hand-arm vibration (HAV) coupling forces hydro-electronic force meter chainsaw vibration exposure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Rottensteiner et al (2012) conducted their research on power saws of the same performance class as that of Stihl MS 362 and found out that the weighted means of vibrations with no regard to tree species were 5.54 m s -2 for Husqvarna 357 XP and 4.26 m s -2 for Husqvarna 372 XP. In another research study conducted by Malinowska-Borowska et al (2012), vibrations on the front chain saw handle and the sum of accelerations in three axes ranged between 5.4 and 5.9 m s -2 . The results of both studies brought higher values than those recorded in our research.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Rottensteiner et al (2012) conducted their research on power saws of the same performance class as that of Stihl MS 362 and found out that the weighted means of vibrations with no regard to tree species were 5.54 m s -2 for Husqvarna 357 XP and 4.26 m s -2 for Husqvarna 372 XP. In another research study conducted by Malinowska-Borowska et al (2012), vibrations on the front chain saw handle and the sum of accelerations in three axes ranged between 5.4 and 5.9 m s -2 . The results of both studies brought higher values than those recorded in our research.…”
Section: Discussionmentioning
confidence: 98%
“…Grip strength of power saw handle affecting the transmission of HAV depends on the operator's experience, work procedures and wood hardness. This means that forces developed by power saw operators are higher in less experienced workers, greater in felling and crosscutting than in delimbing, and greater in tree species of higher wood hardness (Malinowska-Borowska et al 2012;Malinowska-Borowska & Zieliński 2013;Yovi & Yamada 2019). According some other research works Goglia et al 2012;Yovi & Yamada 2019), the level of power saw vibrations is also affected by the chain ten-sion, bar length, fuel amount in the tank and the way of holding the saw.…”
Section: Discussionmentioning
confidence: 98%
“…A notable influence of differing coupling forces for both the chainsaws seems to be limited to the rear handle during the work element "Sawing" and some actions of work element two "Actions related to sawing". Nevertheless, measuring these forces, e.g., through a hydro-electronic force meter [59], provides perhaps the largest potential to enhance future studies.…”
Section: Vibration Exposurementioning
confidence: 99%
“…The transmission is influenced by the grip strength of a chainsaw handle which depends on the worker's work experience, work operation, and wood hardness. According to Malinowska-Borowska et al [12][13][14], grip is stronger in wood of higher hardness, in felling and sawing, Forests 2023, 14, 929 2 of 15 and in less-experienced workers. Hand-arm vibrations differ with respect to the type of wood and are higher in species with higher wood density [15].…”
Section: Introductionmentioning
confidence: 99%